Treasure planet : the junior novelization - Thorpe, Kiki.; Stevenson, Robert Louis, 1850-1894. (New York : Random House, 2002)
In a space version of the classic Treasure Island, the boy Jim Hawkins and the cyborg cook John Silver travel the galaxy in search of Captain Flint's treasure.
At head of title: Disney's.
6.3
3-6
3-6
Keywords: Pirates -- Fiction; Buried treasure -- Fiction; Friendship -- Fiction; Science fiction; Pirates -- Fiction; Buried treasure -- Fiction; Friendship -- Fiction; Science fiction